Sheherazade's Notebook: Editing Textual Dysteleology and Autographic Modernism. Issue 1 (February 2020) - Hulle, Dirk Van
Abstract : Critical editions of 'Complete Works' are typically organized in a teleological manner, using each of the author's published works as an endpoint. In addition to this useful tradition, this article suggests a 'dysteleological' approach. The term 'dysteleology', indicating that evolution has no inherent goal, was coined in the years leading up to Modernism. The existence of vestigial organs served as an example to corroborate the 'dysteleological' view. A writer's unused notes may be regarded as similarly 'vestigial'. They are purposeless from a teleological point of view, but they are crucial elements in the study of creative writing processes ('genetic criticism'). These elements have their rightful place in a scholarly edition, and it is therefore necessary to complement a teleological editorial tradition with a 'dysteleological' approach. To corroborate this argument, the article examines works by James Joyce and Samuel Beckett, as well as by less canonical authors such as Raymond Brulez.